Entropy-Driven 1D Magnetic Carbon Fibers Embedded into 3D Aerogel Enable Broadband Electromagnetic Wave Absorption - Zhao, Tingting; Shao, Shiping; Bi, Ke; Tang, Yunxiang; Wu, Lili; Liu, Jiurong; Wang, Zhou; Wang, Fenglong (Nano-Micro Letters, 2026)
Traditional powder-type electromagnetic absorbers have become inadequate against the intensified radiation across broader frequency ranges, induced by the proliferation of intelligent communication devices. To address this, we present an innovation strategy to assemble spinel ferrites/carbon fibers into a carbon aerogel fabricated via carbonization of a graphene oxide (GO)/2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO)-oxidized cellulose nanofibers (TOCNF) composite aerogel. In the preparation, an entropy-driven design integrated with electrospinning was employed to synthesize the magnetic carbon fibers (MCFs), fully leveraging the complementary advantages of magnetic and carbon materials for optimal impedance matching and attenuation. As a result, the optimized magnetic carbon aerogel (MCA-2), composed of TOCNF, GO, and MCFs, exhibits exceptional broadband electromagnetic wave absorption, with multiple effective reflection loss (RL) peaks (RL ≤ − 10 dB) across the frequency range of 4.8–18 GHz, a minimum RL value of − 54.11 dB, and a maximum effective absorption bandwidth of 7.2 GHz. Additionally, the lightweight MCA-2 aerogel has excellent thermal insulation performance and excellent photothermal performance, which gives it broad application prospects in diverse and harsh environments. Highlights: 1 Entropy-driven design is utilized to enhance the electromagnetic loss synergy mechanism. 2 The combination of 1D fibers and 3D aerogel leverages their complementary advantages. 3 The optimized magnetic carbon aerogel is characterized by strong attenuation and broadband absorption.